Bibliometric Analysis of Global Research on Classroom Incivility - Malodia, Luxmi; Butail, Priya Kumari (Gyan Management Journal, 2024)
Purpose- The purpose of this study is bibliometric analysis of classroom incivility articles published in the journals indexed in Scopus database between 1996 to 25th May, 2023. Design/Methodology/Approach- In bibliometric analysis, a systematic review of classroom incivility using Scopus database has been done. Findings- The publishing trend indicated that the analysis in the field of classroom incivility is in nascent stage. Regarding journals, citation impact, co-authorship, institutions, and authors in this research topic, the United States placed first. Classroom incivility has mainly been associated with nursing field. The most influential journals are Journal of Nursing Education followed by Nurse Educator, Nurse Education Today, and Nursing Education Perspectives. And the most popular keywords are student incivility, social behaviour, incivility and classroom incivility on the basis of their occurrence.